2015
DOI: 10.1007/s10967-015-4653-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of volatile organometallic fission products

Abstract: The ability to perform rapid separations in a post nuclear weapon detonation scenario is an important aspect of national security. In the past, separations of fission products have been performed using solvent extraction, precipitation, etc. The focus of this work is to explore the feasibility of using thermochromatography, a technique largely employed in superheavy element chemistry, to expedite the separation of fission products from fuel components. A series of fission product complexes were synthesized and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…A kinetic model such as a Monte Carlo simulation of single-atom chemistry can predict retention time from adsorption enthalpy and other column specific parameters. To the authors knowledge, this is the second report of enthalpic values for the Ln[hfac] 4 compounds [13]. Comparing to previous studies, values presented here exhibit stronger precision and linearity.…”
Section: Resultsmentioning
confidence: 45%
See 1 more Smart Citation
“…A kinetic model such as a Monte Carlo simulation of single-atom chemistry can predict retention time from adsorption enthalpy and other column specific parameters. To the authors knowledge, this is the second report of enthalpic values for the Ln[hfac] 4 compounds [13]. Comparing to previous studies, values presented here exhibit stronger precision and linearity.…”
Section: Resultsmentioning
confidence: 45%
“…Early studies have shown the utility of volatile β-diketonate ligands as separating agents for rare earth metals [1012]. In previous work, 1,1,1,5,5,5-hexafluoroacetylacetone (hfac) has been shown to produce volatile complexes with lanthanoids [13]. In our work, the use of β-diketonates as a means of volatilization [14] for the possible commercial separations of rare earth elements will be discussed, employing hfac complexes for the entire lanthanide series (except cerium and promethium).…”
Section: Introductionmentioning
confidence: 99%
“…Work is currently underway to further reduce total sample analysis time by modifying the apparatus with a high-temperature furnace for direct injection of chlorides (and eventually oxides) for separation and detection without chemical alteration. Many issues need resolving before a transition to non-volatile sample injection can occur, but even considering the current chemical synthesis step, a sample can be analyzed from its organometallic state in significantly less time, on the order of seconds to minutes, when compared to current solvent extraction or precipitation techniques that can take several hours to perform [3]. …”
Section: Discussionmentioning
confidence: 99%
“…This information is combined with intelligence and law enforcement details to make an informed attribution decision, and it is crucial that the scientific analysis of the debris fed into this cycle is performed with both speed and precision. Current methodologies to separate and quantify nuclear melt glass constituents, including precipitation, solvent extraction, etc., require lengthy analytical techniques that can take several hours to perform [2, 3]; this research aims to reduce the time needed for technical analysis to minutes, or even seconds, by exploiting gas-phase chemistry and a solid injection methodology [4, 5]. Results have indicated for the first time that appropriate instrumentation has been developed to detect fission product complexes using solid-state injection.…”
Section: Introductionmentioning
confidence: 99%
“…A series of multiple, independently controlled, heating elements was chosen to provide the necessary uniformity [12]. The heaters are required to operate independently to be able to control the thermal dynamics of the case depending on the location of the heater on the pipe.…”
Section: Building New Instrumentmentioning
confidence: 99%